2011
DOI: 10.1590/s1806-83242011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of p53, p16 and hTERT in oral squamous cell carcinoma and potentially malignant disorders

Abstract: Oral carcinogenesis is a multi-step process. One possible step is the development of potentially malignant disorders known as leukoplakia and erytroplakia. The objective of this study was to use immunohistochemistry to analyze the patterns of expression of the cell-cycle regulatory proteins p53 and p16INK4a in potentially malignant disorders (PMD) of the oral mucosa (with varying degrees of dysplasia) and in oral squamous cell carcinomas (OSCC) to correlate them with the expression of telomerase (hTERT). Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 23 publications
9
44
0
3
Order By: Relevance
“…Similarly, Patel et al found no correlation between telomerase activation and clinicopathologic parameters in head and neck cancer (42), while Pannone et al reported higher telomerase activity in OSCC than in normal tissue, although this had no clinicopathologic impact (43). The high incidence of hTERT-positive cases in the present study is consistent with other reports (44,45), and the high expression of hTERT in smaller tumors might be indicative of early telomerase activation. Similarly, Chen at al.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Patel et al found no correlation between telomerase activation and clinicopathologic parameters in head and neck cancer (42), while Pannone et al reported higher telomerase activity in OSCC than in normal tissue, although this had no clinicopathologic impact (43). The high incidence of hTERT-positive cases in the present study is consistent with other reports (44,45), and the high expression of hTERT in smaller tumors might be indicative of early telomerase activation. Similarly, Chen at al.…”
Section: Discussionsupporting
confidence: 87%
“…The extent of this immunosuppression is often more profound than that observed in patients with other malignancies, 1 and has been postulated to occur in a hierarchical manner. For example, in the latter case, genetic alterations 2 have been found to affect the primary tumor region more than draining lymph nodes. 1 Moreover, immune effector cells obtained from the peripheral blood of patients with cancer, including HNSCC, have been reported to exhibit Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Abrahao et al studied the oral mucosal biopsies of patients with leukoplakia, erythroplakia, squamous cell carcinoma and hyperplasia of oral epithelium. They showed that the expression of p53 in these conditions increased (27). Mohtasham et al studied 27 patients with fibrosis hyperplasia, 40 with leukoplakia and 28 with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%